Integrasi Al-Quran dan Sains Dalam Taksonomi Pendidikan untuk Mengenal Allah - Miftahul Huda (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2022)
In modern times, when secularism becomes a mentality and spirituality becomes a forgotten thing, life that is shackled by individualist understanding, compassion and friendship has faded, the material and secular solution is through Ma'rifatullah (knowing Allah). The integration of the Quran and science is an important educational alternative to achieve educational goals. The purpose of this article is to analyze the urgency of the Qur'an in science, the concept of ma'rifatullah (knowing Allah) in the Quran, and the role of the Quran and science in the taxonomy of education to know Allah. This research method is a qualitative study of literature. The findings of this study are 1) The urgency of the Quran for science to provide guidance to humans who discuss natural phenomena that aim to make humans know God through the signs of his creation; 2) The concept of ma'rifatullah in the Quran aims for humans to always study all the signs of his greatness on this earth; 3) The role of the Quran and science in the taxonomy of education as a guide so that science is not misused.